Asymptomatic Bacteriuria among Pregnant Women in Addis Ababa, Ethiopia: Prevalence, Causal Agents, and Their Antimicrobial Susceptibility - Ketema Bizuwork; Haile Alemayehu; Girmay Medhin; Wondwossen Amogne; Tadesse Eguale (International Journal of Microbiology)
Asymptomatic bacteriuria (ASBU) is an important health problem among pregnant women, particularly in low-income countries. This study aimed to estimate the prevalence of ASBU and potential risk factors among pregnant women attending antenatal care centers in Addis Ababa. It also aimed to identify causal bacterial pathogens and to assess their antimicrobial susceptibility. A health facility-based cross-sectional study was conducted from March to June 2019. Urine samples from a total of 281 pregnant women with no symptoms of urinary tract infection were tested for ASBU. Women whose urine samples carried greater than or equal to 105 colony-forming units (CFU) of bacteria per milliliter of urine when grown on plate count agar were considered positive for ASBU. Bacterial pathogens were isolated from urine samples of women with ASBU using standard microbiological techniques. Antimicrobial susceptibility of isolates was investigated using the Kirby–Bauer disk diffusion method on Muller–Hinton agar plates. Of 281 pregnant women examined, 44 (15.7%) were positive for ASBU. Logistic regression analysis of the putative risk factors tested in the current study showed that none of them were significantly associated with the occurrence of ASBU (p>0.05). The most frequently isolated bacterial species were Escherichia coli 17 (30.2%), Proteus 13 (23.2%), and Enterococcus 11 (19.6%). All of the E. coli, Citrobacter, and Klebsiella isolates and 84.6% of Proteus were resistant to ampicillin. All bacterial isolates were resistant to at least one of the antimicrobials tested. Resistance to three or more antimicrobials was detected in 15 (88.2%) of E. coli, 13 (100%) of Proteus, and 8 (72.7%) of Enterococcus isolates. Resistance to as many as 7 antimicrobials among E. coli, 8 antimicrobials among Proteus, and 7 antimicrobials among Enterococcus isolates was recorded. Detection of ASBU in a substantial number of pregnant women in this study warrants the need for a detailed study on possible risks of developing symptomatic urinary tract infection (UTI) and associated complications. Multidrug resistance to several antimicrobials was observed in the majority of bacterial isolates. Regular assessment of antimicrobial susceptibility of uropathogens to commonly prescribed antimicrobials and implementation of prudent use of antimicrobials are recommended.